Luminescent chemical sensors for hazardous species detection: elucidation of the sensing mechanisms and selectivity by means of theoretical approaches - Zarate - Bonilla; Ximena (2023)
PROJECT RESULTS: Describe the results of your research in reference to its original and/or modified Project objectives. Specific Goals and the corresponding results 1. To select the families i and ii of selective and non-selective luminescent chemosensors. Based on literature, the systems of interest were selected. Two families of chemical sensors (i) Organic sensors for metal ions. (ii) Inorganic sensors for explosives NACs and VOCs based on luminescent metal-organic frameworks (MOFs). In annex 1, the structures of all systems are shown. In this report we added a series of crown-based molecules which are proposed as systems of interest to be studied. These are the last systems whose computations and study were achieved to conclude completely the execution of the project. 2. To perform the geometry optimizations and frequency vibrational modes analyses of the ground and excited states of the sensor and sensor-analyte systems, in vacuum and incorporating the solvent effects. The geometry optimizations and frequencies calculations of the ground and excited states of the sensors (families i and ii, annex 1) as well as the sensor-analyte systems were performed. So, energy minima structures were obtained to proceed with the following goals. Also, the solvent effect was incorporated. 3. To calculate the thermodynamic parameters that reveal the affinity of the sensor (in family i) for different metal ions. Kinetic parameters associated with electron transfer and radiative deactivation process, such as the electron transfer rate (ket), electron transfer lifetime (????et), radiative rate (krd) and radiative lifetime (????rd) of the emission, were computed employing the emission energy (Ei,j) and the transition dipole moment ( ) to accomplish a quantitative prediction from the competition of the PET process with the radiative emission. Otherwise, thermodynamic parameters such as the binding energy (ΔE), (ΔH), (ΔS), (ΔG) changes in metal/sensor complexation were calculated to analyze the stability of the conformers for the ...